How does the governance of the executive branch operate in democratic Brazil? An analysis of the Center of Government - Cavalcante, Pedro Luiz Costa; Gomide, Alexandre de Ávila (Revista de Sociologia e Política, 2021)
KEYWORDS: center of government; governance arrangement; policy coordination; democracy; Brazil. ABSTRACT Introduction: This paper aims to analyze how the Center of Government (CoG) operates as units responsible for conducting the presidential agenda in contemporary Brazil. Materials and Methods: The study applied the theoretical approach of CoG as a governance arrangement and used qualitative and quantitative data to reach its objective. Besides the bibliographic review on the literature and official documents, the study synthesizes and deepens empirical data and information from a joint research project covering the period of political stability in Brazil, from 1995 to 2014, when elected presidents ended their terms. Results: The empirical findings confirm that CoG is a flexible and dynamic phenomenon. It puts a critical perspective on the normative “good governance” approach that overvalues its technical dimension and neglects its political aspect. Discussion: The inquiry results shed light on the importance of the relation between politics and policy, by demonstrating that CoG’s configuration and functions vary due to multiple causes, each president’s priority policy agenda is implemented with different strategies and; the prioritized policies follow a unique coordination logic inside the Brazilian federal government.